2021
DOI: 10.2147/ott.s317570
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Toxicity Profile of Carfilzomib-Based Regimens for Treatment of Newly Diagnosed Multiple Myeloma: A Systematic Review

Abstract: Carfilzomib (CFZ) is a proteasome inhibitor currently approved for the treatment of relapsed and refractory multiple myeloma (RRMM). Multiple trials are ongoing to evaluate its efficacy and safety in newly diagnosed multiple myeloma (NDMM). The use of CFZ-based two- or three-drug combination regimens as induction for the management of NDMM is an emerging approach. CFZ-based regimens include combinations of immunomodulators, alkylating agents, and monoclonal antibodies along with dexamethasone. In this review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…In our study, the analysis revealed that the risks of hematologic adverse events including anemia, neutropenia, and thrombocytopenia, were significantly higher in the KRd group compared to the Rd group. These findings are consistent with previous RCTs (Dimopoulos et al 2016 ; Hájek et al 2017 ; Stewart et al 2015 ) and observational studies (Imtiaz et al 2021 ; Kawaji‐Kanayama et al 2022 ; Rocchi et al 2021 ) supporting the notion that carfilzomib treatment is associated with an increased risk of hematologic adverse events. The increased risks of anemia, neutropenia, and thrombocytopenia emphasize the need for the monitoring of hematologic adverse events when using carfilzomib.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the analysis revealed that the risks of hematologic adverse events including anemia, neutropenia, and thrombocytopenia, were significantly higher in the KRd group compared to the Rd group. These findings are consistent with previous RCTs (Dimopoulos et al 2016 ; Hájek et al 2017 ; Stewart et al 2015 ) and observational studies (Imtiaz et al 2021 ; Kawaji‐Kanayama et al 2022 ; Rocchi et al 2021 ) supporting the notion that carfilzomib treatment is associated with an increased risk of hematologic adverse events. The increased risks of anemia, neutropenia, and thrombocytopenia emphasize the need for the monitoring of hematologic adverse events when using carfilzomib.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, PSMC2-6 were shown to be more highly expressed at the mRNA and protein level in breast cancer compared with normal breast tissue, which again correlated with worse outcomes ( 60 ). Proteasome inhibitors like bortezomib, carfilzomib, or ixazomib have been very effective in the treatment of multiple myeloma, but resistance to therapy is still a major obstacle ( 13–15 , 27 , 30 ). These drugs target the PSMB5 subunit of the 20S proteasome, and mutations in PSMB5 can confer drug resistance in in vitro models ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The widespread influence of the UPS on cell biology has important implications for human health, as abnormal UPS function is associated with numerous human conditions, including neurodegenerative diseases, autoimmune diseases, and cancer (9,10). For this reason, a number of small molecule inhibitors targeting the UPS were developed for therapeutic intervention, but unfortunately, drug resistance and toxicity remain significant challenges (11,12), especially in hematopoietic cells (13)(14)(15). Novel therapeutic approaches will be required to effectively target the UPS with less toxicity.…”
Section: Introductionmentioning
confidence: 99%